2009
DOI: 10.1093/nar/gkp539
|View full text |Cite
|
Sign up to set email alerts
|

Separation of 1–23-kb complementary DNA strands by urea–agarose gel electrophoresis

Abstract: Double-stranded (ds), as well as denatured, single-stranded (ss) DNA samples can be analyzed on urea–agarose gels. Here we report that after denaturation by heat in the presence of 8 M urea, the two strands of the same ds DNA fragment of ∼1–20-kb size migrate differently in 1 M urea containing agarose gels. The two strands are readily distinguished on Southern blots by ss-specific probes. The different migration of the two strands could be attributed to their different, base composition-dependent conformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Next we prepared our own λ‐phages (supplementary note S2.1 & figure S5) and compared the quality of the genomic DNA to the commercially available λ‐DNA. Denaturing agarose gels showed that our ‘homemade’ λ‐DNA directly released from phage particles is intact (supplementary note S2.2 & figure S6) …”
Section: Methodsmentioning
confidence: 99%
“…Next we prepared our own λ‐phages (supplementary note S2.1 & figure S5) and compared the quality of the genomic DNA to the commercially available λ‐DNA. Denaturing agarose gels showed that our ‘homemade’ λ‐DNA directly released from phage particles is intact (supplementary note S2.2 & figure S6) …”
Section: Methodsmentioning
confidence: 99%
“…In this updated protocol, we use agarose-urea gels to perform denaturing gel electrophoresis [ 23 ]. A detailed protocol using alkaline gel electrophoresis can be found in the fi rst edition of this chapter [ 20 ].…”
Section: Notesmentioning
confidence: 99%
“…Urea-agarose gel electrophoresis The procedure to prepare and run the samples in urea-agarose gel electrophoresis was adapted from Hegedüs et al (2009) with minor modifications. Before loaded on the gels, samples were urea-/heat-denatured.…”
Section: Screening Of Cloned Amplicons By Urea-agarose Gel Electrophomentioning
confidence: 99%
“…Aiming to avoid sequencing all cloned products selected for each consortium, the simple and sensitive DNA fingerprinting analysis method based on urea-agarose gel electrophoresis described by Hegedüs et al (2009) was tested and applied to identify similar cloned amplicons.…”
Section: Screening Of Cloned Amplicons By Urea-agarose Gel Electrophomentioning
confidence: 99%
See 1 more Smart Citation